Early‐Onset Micromorphological Changes of Neuronal Fiber Bundles During Radiotherapy. Issue 1 (2nd December 2021) - Liu, Jin; Wang, Wenjuan; Zhou, Yanfei; Gan, Chen; Wang, Tengfei; Hu, Zongtao; Lou, Jianjun; Wang, Hongzhi; Yang, Li‐Zhuang; Wong, Stephen T.C.; Li, Hai
Abstract : Background: Patients receiving cranial radiation face the risk of delayed brain dysfunction. However, an early medical imaging marker is not available until irreversible morphological changes emerge. Purpose: To explore the micromorphological white matter changes during the radiotherapy session by utilizing an along‐tract analysis framework. Study Type: Prospective. Population: Eighteen nasopharyngeal carcinoma (two female) patients receiving cranial radiation. Field Strength/Sequence: 3.0 T; Diffusion tensor imaging (DTI) and T1‐ and T2‐weighted images (T1W, T2W); computed tomography (CT). Assessment: Patients received three DTI imaging scans during the radiotherapy (RT), namely the baseline scan (1–2 days before RT began), the middle scan (the middle of the RT session), and the end scan (1–2 days after RT ended). Twelve fibers were segmented after whole‐brain tractography. Then, the fractional anisotropy (FA) values and the cumulative radiation dose received for each fiber streamline were resampled and projected into their center fiber. Statistical Tests: The contrast among the three scans (P1: middle scan–baseline scan; P2: end scan–middle scan; P3: end scan–baseline scan) were compared using the linear mixed model for each of the 12 center fibers. Then, a dose–responsiveness relationship was performed using Pearson correlation. P  < 0.05 was considered statistically significant. Results: Six of the 12 center fibers showed significant changes of FA values during the RT but with heterogeneous patterns. The significant changes along a specific center fiber were associated with their cumulative dose received (Genu: P1 r  = −0.6182, P2 r  = −0.5907; Splenium: P1 r  = 0.4055, P  = 0.1063, P2 r  = 0.6742; right uncinate fasciculus: P1 r  = −0.3865, P2 r  = −0.4912, P  = 0.0533; right corticospinal tract: P1 r  = 0.4273, P  = 0.1122, P2 r  = −0.6885). Data Conclusion: The along‐tract analysis might provide sensitive measures on the early‐onset micromorphological changes. Level of Evidence: 2 Technical Efficacy: Stage 3